Structure of 2-(2-(anthracen-9-ylmethylene)hydrazinyl)-4-(3-methyl-3-phenylcyclobutyl)thiazole by combined X-Ray crystallographic and molecular modelling studies - Karakurt, Tuncay; Cukurovali, Alaaddin; Kani, Ibrahim (Taylor & Francis Ltd, 2020)
A single crystal of 2-(2-(anthracen-9-ylmethylene)hydrazinyl)-4-(3-methyl-3-phenylcyclobutyl)thiazole (C29H25N3S) containing anthracene, thiazole and cyclobutane rings has been synthesised. The synthesised crystal structure was characterised using IR, H-1-NMR and C-13-NMR spectroscopic and X-Ray analysis techniques. In the crystal, neighbouring molecules formed chains along [110] by interconnecting with N-H center dot center dot center dot N hydrogen bonding and pi-pi interactions. The geometrical parameters of the title compound were optimised by Gaussian 09 software in the gas phase and Quantum-Espresso software under Periodic Boundary Conditions (PBC) in the solid phase. Theoretically, IR, NMR spectra, Mulliken, NPA and AIM atomic charges, Hirshfeld surface and frontier molecular orbitals (FMOs) of the title compound were examined. Using the Hirshfeld surface and two-dimensional (2D) fingerprint graphics, the presence of intermolecular interactions in the crystal packing were analysed. The energies of these interactions and their distribution on the crystal structure were shown graphically. In general, it was seen that theoretical calculations were consistent with X-Ray results.
Keywords: X-Ray; Quantum-Espresso; solid phase; PBC; Hirshfeld surface